Peran Literasi di Usia Dini dalam Membangun Kemampuan Bahasa Anak Panti Asuhan: Studi Kasus di Yayasan Hati Ibu, Medan - Telaumbanua, Putri Handayani; Ginting, Bengkel; Ritonga, Fajar Utama (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2023)
This article aims to discuss the importance of a literacy approach in early childhood to help shape children's language abilities in orphanages. The research was conducted using literature review methods and field studies on children in the orphanages. The results of the study indicate that the literacy approach in early childhood successfully enhances reading, writing, and speaking abilities in the Indonesian language among children in the orphanages. The methods of early childhood literacy approach used include using storybooks and literacy materials suitable for children's age, as well as employing enjoyable and interactive learning methods. Meanwhile, the availability of age-appropriate literacy materials and collaboration between orphanages, government, educational institutions, and the community are crucial factors in the success of early childhood literacy education programs. Therefore, it is important for stakeholders to increase attention and support in providing access to good literacy education for children in orphanages, so that children can have proficient language skills and be ready to actively participate in society